LEARNING VOCABULARY TROUGH CAKE APPLICATION - fitria, masya nurul; Maulida, Ratih Puspa; Fitri, Adhelia; Auliana, Lindi; Khomarudin, Khomarudin (Universitas 17 Agustus 1945 Semarang, 2023)
Learning new information and abilities is the process of education. Learning English is a skill-based learning experience that necessitates a variety of ways and tactics. Technological innovations have had a significant impact on current education. Technology is the most recent solution to the issues of learning English. As English language learning methods improve, cake completes an innovative method of language learning on a mobile phone base. The goal of this study is to look into how Cake apps can help students improve their vocabulary at IAIN Syekh Nurjati Cirebon. This study employs a pre-experimental research design with a pre-test. Five students will participate in this study. The research instruments were tests and questionnaires used to answer the study questions. How does the vocabulary of pupils change as a result of using Duolingo? The students' scores are raised as a result of the quanlitative data. The end product is anticipated to provide teachers and students with knowledge on having in-depth language learning practice in a convenient style.Â